Are we disabled among the disabled?: disability awareness among University of Malaya students / Azri Ardila Nor Azizi, Mohd Nazir Rabun and Nur Amira Syafiqah Badarin - Nor Azizi, Azri Ardila; Rabun, Mohd Nazir; Badarin, Nur Amira Syafiqah (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Accessibility of Person with Disability (PWD) in institutions of higher learning has brought much attention for university to raise the disability awareness in the campus community. The disability awareness is crucial in promoting the rights and provides equal opportunities to ease the mobility of PWD in university. This study examined the factors related to level of disability awareness among students in University of Malaya. Purposive samples of 269 of undergraduate and postgraduate students were asked to answer the questionnaire in their convenient time in regards with the level of disability awareness. The association between students’ demographic background in terms of education level and gender was examined to determine the level of disability awareness among students in University of Malaya. Surprisingly, it was found that the students of University of Malaya showed a moderate level of disability awareness Thus, the study provides a strong evidence that it is crucial for the university administration to embark on more effective campaingn social work programmes among students in the university in which the disability awareness was not at its highest level since the disabled-related issues were only rise since the Paralympic Games 2016. Since the number of disability is expected to increase, therefore, it is crucial for more intervention programmes and comprehensive discussion to be advocate to raise the disability awareness among the society.